Pemberdayaan dalam Perspektif Al-quran - Harahap, Masrul Efendi Umar (Fakultas Dakwah dan Ilmu Komunikasi, 2019)
PEMBERDAYAAN DALAM PERSPEKTIF AL-QUR’ANOleh : Masrul Efendi Umar Harahap, M. Sos abstractDa'wah as one of the ways in community empowerment efforts, has many advantages because it does not study from the perspective of religion alone, but examines from various sources that can be used. Empowerment in the Koran includes economic fields such as through donations, alms, almsgiving, environmental empowerment, education, social, environment and so on. Islam teaches its people through the Qur'an. Islam teaches its people to look after each other, strengthen, educate for world life and the hereafter happiness. If seen empowerment in the context of da'wah then there are 4 functions of da'wah relating to empowerment, namely: i'tiyadi, muharriq, iqaf, and tahrifKey Word : Pemberdayaan, Al-Qur’an